A typology of interpersonal stalking - Wright, James A. (Journal of interpersonal violence, 1996)
This article offers a structure for trying to distinguish between different types of stalking and for assessing the outcome of these different types of incidents. Using a law enforcement experiential paradigm, 10 stalking victims pilot-tested a questionnaire of 148 items. Revisions provided a 46-item checklist. In addition, 30 cases were used to pilot-test a typology of stalking based on the nature of the relationship-nondomestic or domestic; the content of communication-nondelusional or delusional; level of aggression-low, medium, or high; level of victim risk; motive of stalker; and outcome of case. Clinicians, investigators, judicial, and policy staff can utilize data from the Stalking Incident Checklist in their respective roles to provide for safety and protection of the victim and treatment and containment of the stalker